(untitled) (Journal of humanities and social sciences exploratio, 2026)
This paper explores the motivations, current dilemmas, and breakthrough paths for the digital transformation of human resources in the public sector within the context of digital government. With the advancement of the Fourth Industrial Revolution, driven by artificial intelligence, big data, and cloud computing, the construction of digital government has become a strategic choice for modernizing the national governance system and capacity. As a core element of government operations, the digital transformation of human resources in the public sector is crucial for enhancing governance effectiveness. Currently, this transformation faces challenges such as data silos, a shortage of compound talents, tensions between traditional management models and digital requirements, and lagging institutional support. The paper proposes breakthrough paths, including establishing a user-centric digital service philosophy, cultivating data thinking and digital leadership among leaders, optimizing the performance evaluation mechanism for civil servants, constructing an integrated and intelligent human resource management information platform, and establishing a four-pronged talent mechanism encompassing recruitment, cultivation, integration, and retention. The aim is to provide solid human resource support for the construction of a digital government.